Investigation on the use of metalens for ultrasound imaging in non-destructive testing - Xu, Jia Wei (Nanyang Technological University, 2021)
Non-Destructive Testing is the technology to examine and analyse the structural integrity without causing physical damages and chemical changes to the material being examined. Ultrasonic testing is one of the common and widely used method of NDT adopted to examine component defect and discontinuities some distances from the surface of the material. This study investigates the possibilities of using a lower frequency transducer in the presence of metamaterial lenses to better improve the detection of defects.Experiments carried out to particularly study the signal properties of the lower frequency transducer in the presence of metamaterial lens were compared to that of the higher frequency transducer used in the previous work. This is to study and explore the behaviours of signal profiles when both probes are used to scan over the presence defect in a component. Metamaterial lenses are bundles of straws of different lengths and diameters. They serve the purpose of amplifying evanescent waves and reduce scattering effect and the effect of beam spread during the scan of specimens.The experiment simulates an inspection conducted on a component with an internal defect. Water serves as the component being inspected. An aluminium block width of 25mm is placed and immersed in the water, serving as a defect presence. Similar to that of previous work, lens 2 with shorter length of 40mm and a diameter of 6mm produced a better signal behaviour when it is being used together with the 500khz transducer. The second experiment was also done to examine how the lenses enhance the detection of defects when two defects are coming to close to each other. There were 7 specimens made of aluminium with each specimen having two through holes separated at different distances apart.There are several valuable experimental observations made throughout the experiment and information on future work is also discussed.